ANALISIS KERAGAAN SISTEM USAHATANI BERBASIS LAHAN - R Sunsun Saefulhakim; Dyah Retno Panuju; Lutfi I Nasoetion (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 1999)
Efficiency and productivity are important terms in understanding the performance of the farming system. The landbased farming system is generally efficient and productive if it operates in a certain range of landholding scale. This study assumed that efficiency and productivity are related to farmland holding scale, land fragmentation, and cropping diversification. In a land-based farming system, land ownership holding scale and fragmentation and cropping diversification are assumed to have specific correlation. This study was conducted under a cooperation work between Research Institute of Bogor Agricultural University and Agency for Research and Development of Department of Agriculture, in research titled